Challenges and Barriers In Research Writing-Dental House Officers’ Perspective: Research Writing Barriers - Ahmad, Rana Ammar; Mumtaz, Maryam; Aqeel, Rummana; Awais, Faiza; Rana, Muhammad Haseeb; Khan, Nishwah; Naeem, Sajid; Qamar, Khezran (Pakistan Journal of Health Sciences, 2024)
Professional development in medical and dental sciences requires research. There was limited information about the research barriers faced by students in this region. Objective: To find out the common challenges and barriers faced by the house officers when writing research proposals. Methods: Dental house officers of 3 private dental colleges in Punjab were recruited for the cross-sectional study. Data collection was done using a self-administered, structured questionnaire. Closed-ended questions were designed to cover 4 domains of research barriers, e.g., personal, educational, environmental, and technical. 16 items of perceived research conduction barriers on three-point Likert scale (Disagree, Agree and Neutral) were included. Results: The most frequently evident barriers were personal 2.26 ± 51.8% and educational 2.00 ± 51.8%, followed by environmental 1.96 ± 51.8% and technical 1.87 ± 51.8%. House officers disagreed that they were not interested in research writing. 68.9% didn’t have any undergraduate research writing experience. 53.6% believe that research contributes to professional development. 45.0% disagree that they will not do research during a house job. 51.4% believed that there was a lack of time for conducting research. 73.4% regarding lack of financial funding was reported. 57.7% believed that inadequate equipment and facilities were the main hurdles in conducting research. 64.4% of participants were of the view that they lack knowledge. 59.9% believed that supervisors do not give adequate time. Conclusions: In order of importance, the most commonly reported barriers in writing research proposals by the dental house officers were personal and educational, followed by environmental and technical barriers.